Myopia and Near Work Activity in Maderassa Children in Karachi - Sami-ur-Rehman Khan, Manzoor A. Mirza, Tahir Masaud Arbab, Saeed Iqbal (Pakistan Journal of Ophthalmology, 2008)
Purpose: To determine the relationship of myopia and near work in Maderassa children in Karachi. Material and Methods: A cross-sectional study of 300 maderassa children aged 9 to 17 years was conducted in 3 Maderassa in Karachi. Cycloplegic Refraction, keratometry, and biometry measurements were performed. In addition the number of year’s child was studying in this maderassa, and near work activity (reading in hours per day) was also asked. Results: Of the 300 children in the sample, 118 (39.3%) were myopes, 33 (11%) hypermetropes, and 149 (49.6%) emmetropes. Myopia was the most common type of refractive error. The average refractive error of these myopic eyes was -2 D. Mild myopia ( -0.50 to -2.99 D) was found in 59.3 % of children, moderate myopia ( -3.00 to -5.99 D) in 30.5 % and severe myopia ( more than -6.00 D) in 10.1 %. Association of near work activities and myopia emerged, as we divided the students in to 2 groups, Group A children who were in the Maderassa for more than 3 years, consists of 120 children and group B children who were in the Maderassa for less than 3 years consist of 180 children. It was found that 50.83% of children in Group A had myopia and the average refractive error of these myopic eyes was -3 D. 31.66 % of children in Group B had myopia and the average refractive error of these myopic eyes was -1 D. Conclusions: The study results suggest that myopia is a rather common refractive error in Maderassa students. Findings also indicate that myopia is probably correlated with educational level and excessive near work.